Kajian Faktor yang Mempengaruhi Kualitas Tutorial Tatap Muka di Universitas Terbuka Medan - Sihar Pandapotan (Universitas Negeri Medan, 2014)
The research was motivated by the implementation of face-to-face tutorial in UPBJJ-UT Medan that is still considered to have several problems, such as the declining of student attendance rates in several study groups (pokjar). This study aimed to: (1) describe the implementation of face-to-face tutorial (TTM) and the criteria of the tutorial systems in UPBJJ-UT Medan, (2) analyze the factors that determine the quality of tutorial, and (3)identified factors that impede the quality of tutorial. The researchis descriptive with a qualitative approach. Data were collected through interviews and distributing questionnaires to 75 respondens who were randomly assigned; and analyzed by qualitative descriptive. The results showed that : (1) TTM held in UPBJJ-UT Medan through the stages of the recruitment of tutors, tutor training, delivery of instructional materials timely, and tutorial monitoring. While the geographical factors used as criteria for the establishment of tutorial areas with the system model block, semi-block and regular. (2) supporting factors of tutorial quality: (a) tutors, (b) instructional materials, (c)students, (d) tutorial location, and (e) the examination system; and (3) inhibiting factors include: (a) distance, (b) age, (c) time, (d) economic and (e) cultural-religion.